2021
DOI: 10.1001/jamaoto.2021.2019
|View full text |Cite
|
Sign up to set email alerts
|

Total Laryngectomy Volume During the COVID-19 Pandemic

Abstract: 4.Graboyes EM, Halbert CH, Li H, et al. Barriers to the delivery of timely, guideline-adherent adjuvant therapy among patients with head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In the secondary analysis of patients eligible for recruitment in an ongoing study, there was no evidence of an increase in diagnoses at advanced stage in the periods following the first pandemic wave. This is in line with a recent finding of no increased total laryngectomy volume, reserved for advanced cases, during the COVID-19 pandemic ( 30 ). Although these findings indicate no evident stage migration, it should be considered that the 10-month period after the start of the pandemic may still be limited to observe any change in the distribution of stages at diagnosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the secondary analysis of patients eligible for recruitment in an ongoing study, there was no evidence of an increase in diagnoses at advanced stage in the periods following the first pandemic wave. This is in line with a recent finding of no increased total laryngectomy volume, reserved for advanced cases, during the COVID-19 pandemic ( 30 ). Although these findings indicate no evident stage migration, it should be considered that the 10-month period after the start of the pandemic may still be limited to observe any change in the distribution of stages at diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…Several previous studies that reported COVID-19-related reductions in HNC admissions and diagnoses ( 12 – 16 , 31 , 32 ) were hospital-based studies, conducted on a relatively limited population, focused on the first pandemic wave only, and did not account for temporal trends in HNC detection. The reported reductions in HNC referrals and diagnoses in the first pandemic months varied from 12% to up to 60% in different contexts and populations ( 13 , 15 , 16 , 30 , 31 ). In this study, accounting for temporal trends over a relatively long period and seasonal (likely holiday-related) fluctuations in HNC admissions, we found a decline of 28% in incident HNC admissions during the first pandemic wave, which was almost completely recovered in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights how much breast cancer diagnosis relies on screening programmes which have suffered badly as a result of the pandemic in England36 and internationally 39. In England, head and neck cancers (HNC) saw a 10.2% (95% CI 7.6% to 12.7%) reduction in diagnosis, while studies in other geographies showed wide differences in the measures’ impact of the pandemic on HNC: a study in Ontario, Canada, found no evidence of a reduction in HNC diagnosis following an initial drop in the 6 weeks following lockdown,40 a clinic in Italy had just a 3.7% reduction in HNC,41 a 14% reduction in Belgium,29 a clinic in California showed a 22% reduction42 and a Cancer Centre in the North of England reported a 33% reduction in HNC cases 43. There is further international evidence of the impact of COVID-19 on interventions down the pathway, with reductions in radical cancer surgeries in two major cancer hubs in England and Italy 44…”
Section: Discussionmentioning
confidence: 99%